Halophilic Bacteria as Promising Biocatalyst Producers: A Review on Enzyme Production - Aini, Diah Miftahul; Balqis, Solina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Halophilic bacteria, a group of extremophiles adapted to high-salinity environments, have emerged as valuable sources of relevant biocatalysts. This review aims to compile and analyse current knowledge on the enzymatic potential of halophilic bacteria. Using a systematic literature review as its primary methodology to collect, examine, and integrate academic findings on halophilic bacteria as promising sources of biocatalysts. This review highlights that halophilic bacteria possess remarkable physiological and biochemical adaptations that enable them to survive osmotic stress, with recent advances in genetic engineering and synthetic biology enhancing their enzyme production and functional efficiency. These findings underscore their potential as robust and efficient biocatalysts for sustainable industrial applications. In conclusion, halophilic bacteria represent valuable resources for biotechnology, particularly in extreme conditions where conventional enzymes fail. Future research should focus on in-depth genomic and proteomic analyses, metabolic engineering for optimized enzyme yields, industrial-scale feasibility studies, environmental impact assessments, and cross-disciplinary collaborations to fully harness their capabilities in real-world applications.